Modelo multicritério de apoio à definição do nível alvo da maturidade em ouvidoria pública do instituto federal do paraná - Alves, Luciane Fátima (2023)
In the search to consolidate the process of improving the management of public ombudsman units, the Compttose General of the Union proposed the Maturity Model in public ombudsman as an instrument for measuring the organizational stage of these units, mapping their competencies and capacities, to stimulate their continuous improvement. Given the limitations found in the model, the low number of employees of the ombudsman's office of the Federal Institute of Paraná and the lack of a methodology, within the institution, that meets the gaps identified in the model, this study proposes the application of the technique of Multicriteria Analysis of Decision Support with the objective of supporting the managers of the institution in defining the target level of maturity of its ombudsman. The study was characterized as exploratory research, in the stages of the applied bibliographic and documentary survey, which gathered the data for the theoretical basis of the investigation; also as descriptive research, because it reported the path adopted in the application of the multicriteria methodology, describing the data obtained and their respective analyses; and with a mixed approach, because it adopted qualitative and quantitative approaches, both in the adoption of bibliographic research and in the multicriteria methodology. The study resulted in the construction of a multicriteria model to meet the proposed objective, validated by the institute's decision-makers, and by which it was possible to diagnose the current basic maturity of the institution's ombudsman and support the definition of its sustained target level, from the perspectives of its managers. Thus, the multicriteria methodology demonstrated, in an applied and effective way, its feasibility for solving the research problem